Market Structure and Competitiveness of Indonesian Unmanufactured Tobacco in the International Market - Siti Rochaeni; Rahmila Maulisza; Dewi Rohma Wati (International Journal of Economics, Business and Innovation Research, 2024)
In Indonesia, tobacco, main commodities of cigarette industry, has a contradictory position. It came with health issues, but on the other side it made big contributions in revenues for the country. This research aimed to analyze the market structure and competitiveness of Indonesian unmanufactured tobacco in the international market. The secondary data collected by time series from 2005 to 2020, and analyzed through Concentration Ratio (CR), Herfindahl Hirchman Index (HHI), Revealed Comparative Advantage (RCA), and Trade Specialization Index (TSI). The results showed that unmanufactured tobacco commodities indicated the features of monopolistic market structure (CR = 34.03%; HHI = 492.00). By RCA, Indonesia considered possessed a strong competitiveness as tobacco exporter (RCA1 = 3.03; RCA2 = 1.19; RCA3 = 1.40). But on the contrary, by TSI, Indonesia was still in the import substitution stage (TSI1 = -0.10; TSI2 = -0.57; TSI3 = -0.30), indicating low level of competitiveness. Keywords unmanufactured tobacco; market structure; competitiveness; comparative advantages; competitive advantages